APLIKASI MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA DIKLAT MENGGUNAKAN HASIL PENGUKURAN - Oriza Candra; Doni Tri Putra Yanto; Nazirul Imam (UIR Press, 2020)
Student learning outcomes in learning is very important to be used as a reference for indicate of successful in learning. The observation result at grade X TITL SMKN 1 Pariaman identified that there are several problems that influence student learning outcomes, such as communication in learning process just one - way, the students did not master the contents, students tend to be afraid to ask the question, the students out of the classroom and talk with their seatmate. Consequently most of student learning outcomes were under KKM that seen from the pretest. To overcome this problem, research is conducted which seeks to see an increase in student learning outcomes in subjects